Outstanding Achievement in Outreach/Community Service - Krambia-Kapardis, Maria (My University, 2026)
Awarded from the Head office in New York, the ACFE’s 2019 Achievement in Outreach/Community Service Award for “being an active contributor to her community and is committed to helping improve the quality of life where she lives and works
Keywords: Sciences